Comparative Antiproliferative and Antiangiogenic Activity of Cacao Preparations (P06-048-19). (13th June 2019) - Li, William; Li, Vincent; Ward, Catherine; Müller, Werner; Ackermann, Maximilian
Abstract: Objectives: Multiple lines of evidence show the benefits of cacao on inflammation and cardiovascular disease. The relationship between cacao and cancer is less well defined. Cacao contains bioactive compounds with antiangiogenic properties, such as procyanidins and catechins. Angiogenesis, blood vessel formation, is critical for tumor growth and validated target in cancer therapy. We studied the antiangiogenic and anti-tumorigenic potential of two commercially available 100% cacaos (Valrhona and De Zaan). Methods: L5178y mouse lymphoma cells were incubated with different concentrations of cacao (0, 0.1, 0.3, 1, 3, and 10 µl/ml). The calorimetric methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay was applied to assess cell viability. Human umbilical vein endothelial cells (HUVECs) were grown as monolayer in Matrigel and embedded with cacao preparation. Image analysis of capillary tubes was performed and vessel diameter and intervascular length were quantified. Results: Compared to untreated control cells, cacao preparations significantly inhibited the growth of mouse lymphoma cells in a dose-dependent manner. De Zaan had greater anti-tumor activity than Valrhona by 29.4% (p = 0.001). Cacao also inhibited angiogenesis. In the tube formation assay, increased intervascular length between individual vessel segments indicates a lower vessel density. Differential activity was observed between De Zaan which increased intervascular length by 33% (p = 0.01) compared to Valrhona, which showed a 20% increase in intervascular length (p = 0.07). Vessel diameters were also reduced by 31.8% (Valrhona, p = 0.001) and by 10% (De Zaan, p = 0.16). A reduction in tumor vessel diameters is a characteristic of clinical antiangiogenic therapy. Conclusions: Cacao exhibits potent antiangiogenic bioactivity that has potential to suppress tumor angiogenesis through dietary intake. In addition, cacao inhibited the growth of lymphoma cells. Different cacao varieties possess different levels of bioactivity. This study is one of the first to directly test cacao rather than individual cacao bioactive compounds. Whole food preparations may contain greater bioactivity than individual components. Funding Sources: Flora Thornton Foundation, The Walter and Phyllis Borten Foundation.